"Real-time" genetic monitoring of a commercial fishery on the doorstep of an MPA reveals unique insights into the interaction between coastal and migratory forms of the Atlantic cod. (15th December 2017) - Johansen, Torild; Westgaard, Jon-Ivar; Seliussen, Bjørghild B; Nedreaas, Kjell; Dahle, Geir; Glover, Kevin A; Kvalsund, Roger; Aglen, Asgeir
Abstract: With the decline of many of the world's fisheries, increased regulation, including marine protected areas (MPA), forms an increasingly important role in promoting sustainable resource use. Here, we present a novel "real-time" genetic monitoring programme used to protect the depleted Norwegian coastal cod stock (NCC) in an MPA during the spawning season, while a fishery targeted at the sustainable Northeast Arctic cod stock (NEAC) operates immediately outside. In the period 2009–2016, >6800 cod from the fishery were genotyped with the PanI locus that is discriminatory between these two stocks. The estimated fraction of NEAC increased during the study period until 2014; however, it did not exceed 70% for any sustained period. Therefore, the MPA remained closed for commercial harvest. Genetic analysis of eggs revealed a distinctly lower fraction of NEAC than in the catch from the adult stock, both immediately outside and within the MPA itself. We suggest that this discrepancy is likely to reflect differences in spawning areas used by NCC and NEAC. Estimated fractions of NEAC/NCC using PanI, otolith classification, and 39 single nucleotide polymorphisms were similar, thus validating the use of PanI to estimate NEAC/NCC composition.